Da'wah and Change in Urban Areas: A Study of the Darusshofa Islamic Study Group in Medan City - Anggun Dwi Nanda Nasution; Abdullah; Phan Thanh Huyen (Program Studi Komunikasi dan Penyiaran Islam Fakultas Dakwah Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2026)
This study aims to analyze how Majelis Taklim Darusshofa, an Islamic da'wah group, carries out da'wah, the methods they use, and how they help bring about social change in the city of Medan. As an Islamic da'wah institution operating in an urban environment, Majelis Taklim Darusshofa faces urban dynamics characterized by high population mobility, socio-cultural diversity, and the increasing use of digital technology. This study uses qualitative and descriptive methods, with data collected through participatory observation, in-depth interviews with administrators and congregants, and documentation of activities taking place at the majelis taklim. The research findings show that Majelis Taklim Darusshofa uses flexible da'wah methods, such as the use of digital media, relevant religious guidance according to the needs of city residents, and strengthening community solidarity in response to the changes brought about by modern urban life. Their da'wah not only spreads Islamic values but also plays a role in shaping the religious character of the city's residents, strengthening social resilience, and directing behavioral changes in a more positive direction. In short, the Majelis Taklim Darusshofa has a strategic function in maintaining the continuity of religious life while also serving as a space for social transformation amidst urban change in Medan.